The ‘Sinfluencer’ Phenomenon in Surakarta: An Analysis of the Impact of Endorsement Lack of Transparency on Consumer Trust - Rahayu, Ima; Dhany Efita Sari (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the impact of non-transparent endorsements (sinfluencer phenomenon) on consumer trust in Surakarta. Using a qualitative case study approach, data were collected through in-depth interviews, observation, and documentation involving social media users and influencers. The findings reveal that a lack of transparency reduces consumer trust, increases skepticism, and affects purchasing decisions. Consumers become more cautious and critical when evaluating promotional content. This study highlights the importance of transparency in maintaining credibility and sustaining long-term relationships between influencers, brands, and consumers in digital marketing practices.